MANGROVES OF KETI-BUNDER, INDUS DELTA: A PRESENT STATUS - Farooqui, Zafar (European Scientific Journal, ESJ, 2014)
The paper is the part of recent thesis submitted to Institute of Karachi. The topic of thesis is ‘studies on mangrove ecosystem with respect to biodiversity, productivity and nutrients dynamics”. In this paper we present the present status of Indus delta mangroves with rspect to the present studies done by the author. The present research article constitutes a report of litter production and decomposition rates of Avicennia marina and Rhizophora mucronata leaves from Hajambro creek, Indus delta located near active Indus river mouth and compared. The total litter production was 4.78 tonnes ha-1 year-1. Extrapolating the data for the whole mangrove covered area in the Indus delta; the figure comes to about 1.2 x 106 tone y-1. The percent contribution of different components of the litter varies, with leaf-litter being the most dominant component (about 50 %) of the total litter biomass. The rate of decomposition was species specific, A. marina leaves decomposed faster (p<0.001) than the R. mucronata. The time in days required for the loss of the initial dry mass (t50) was 49.55 days for the A. marina and 44.43 days in case of R. mucronata. The initial loss may represent the leaching of dissolved organic matter. The results showed that the breakdown of the leaf litter is species dependent.